The surface oxidation behavior of Ni-45.16%Ti shape memory alloys at different temperatures - Dagdelen, Fethi; Ercan, Ercan (Springer, 2014)
The isothermal oxidation behavior of Ni-45.16%Ti (composition in atomic percent) alloy was investigated by thermogravimetric analysis, and differential scanning calorimeter (DSC) methods. It was found that Ni-rich NiTi alloy exhibits a different oxidation behavior at temperatures above 400 A degrees C in oxygen atmosphere. The alloy was exposed to oxygen atmosphere isothermally, i.e., between 400 and 800 A degrees C, for 1 h. A gravimetric method was used to determine the oxidation kinetics and it was seen that the oxidation constant increases significantly with isothermal temperature. The activation energy of oxidation reaction for NiTi alloy was determined to be 65.47 kJ mol(-1). According to DSC measurements, the transformation temperature of alloy (M (s), M (f), A (s) and A (f)) was increased and also R phase disappeared above 500 A degrees C. The formal oxides were determined by means of SEM-EDX measurements and obtained oxides are TiO and TiO2 oxides.
Keywords: Ni-rich NiTi shape memory alloy; Oxidation kinetics; Isothermal oxidation